Neurologic disorders are prevalent in HIV-positive outpatients in the Asia-Pacific region - Wright, E.; Brew, B.; Arayawichanont, A.; Robertson, K.; Samintharapanya, K.; Kongsaengdao, S.; Lim, M.; Vonthanak, S.; Lal, L.; Sarim, C.; Huffam, S.; Li, P.; et al. (2008)
Background: A total of 8.3 million HIV-positive people live in the Asia-Pacific region. The burden of HIV-associated neurocognitive impairment and symptomatic sensory neuropathy in this region is unknown. Methods: Between July 2005 and March 2006, we undertook a cross-sectional study at 10 sentinel sites within eight Asia-Pacific countries to determine the prevalence of moderate to severe HIV-related neurocognitive impairment and symptomatic sensory neuropathy. We clinically assessed and administered sensitive neuropsychological and peripheral neuropathy screening tools to 658 patients infected with HIV. Univariate and logistic regression analyses were applied to the data. Results: The results showed that 76 patients (11.7) (95 CI 9.3-14.2) were significantly neurocognitively impaired, 235 patients (36.4) (95 CI 32.7-40.2) were depressed, and 126 patients (19.7) (95 CI 16.6-22.8) had either definite or probable symptomatic sensory neuropathy; 63 of this last group had exposure to stavudine, didanosine, or zalcitabine. Several potential confounders including depression (OR 1.49, 95 CI 0.88-2.51, p = 0.11) and prior CNS AIDS illness (OR 1.28, 95 CI 0.50-2.89, p = 0.54) were not significantly associated with neurocognitive impairment. Conclusions: A total of 12 of patients had moderate to severe HIV-related neurocognitive impairment, 20 of patients had symptomatic sensory neuropathy, and 36 of patients had evidence of depression. This study provides a broad regional estimate of the burden of HIV-related neurologic disease and depression in the Asia-Pacific region.